Analysis of Marketing Mix on Purchase Decision of The Body Shop Product in Pejaten Village Mall Outlet - Ariani, Nani; Farahnur, Viona Prameswari (International Humanities and Applied Science Journal, 2020)
This research is a quantitative descriptive research that aims to determine the effect of marketing mix on purchasing decisions. The population in this research was consumers of The Body Shop in Pejaten Village Mall. The sample size was taken by 100 respondents, by accidental sampling method. Data collection is done through questionnaires. Analytical technique used is the method of analysis PLS (Partial Least Square). The results of this study show that the product and price have no significant influence on purchasing decisions. While the promotion and distribution have significant influence on purchasing decision.